OP55 Socioeconomic Inequalities in Childhood Exposure to Secondhand Smoke Before and after Smoke-Free Legislation in three UK Countries. (17th September 2012) - Moore, GF; Currie, D; Gilmore, G; Holliday, JC; Moore, L
Abstract : Background: Secondhand smoke (SHS) exposure is higher among children from lower socioeconomic status (SES) families, contributing to the intergenerational reproduction of health inequalities. Legislation prohibiting smoking in enclosed public places was introduced in all UK countries between 2006 and 2007. Although opponents argued that it would displace smoking into the home, legislation has been associated with reduced childhood SHS exposure and increased prevalence of smoke-free homes. In some UK countries however, trends towards widening inequality in childhood SHS exposure have been reported following legislation. This paper combines datasets from 3 UK countries to examine socioeconomic patterning in childhood SHS exposure and smoking restrictions in homes and cars pre- and post-legislation. Methods: We conducted a repeat cross-sectional survey of 10, 867 schoolchildren in 304 primary schools in Scotland, Wales and Northern Ireland. Children provided saliva for cotinine assay, completing questionnaires before and 12-months after legislation, including the Family Affluence Scale (a measure of socioeconomic status), and reports of smoking restrictions in homes and cars. Multinomial regression analyses assessed differences between survey years in SHS exposure and private smoking restrictions, with interaction terms to assess SES patterning in changes. Results: SHS exposure was highest, and private smoking restrictions least frequent, among lower SES children pre- and post-legislation in all countries. Proportions of samples containing <0.1ng/ml (i.e. undetectable) cotinine increased significantly (RR=1.63; 95%CI=1.45 to 1.83), from 31.0% to 41.0%. Although across the SES spectrum, there was no evidence of displacement of smoking into the home, socioeconomic inequality in the likelihood of samples containing detectable levels of cotinine increased (RR=1.10; 95%CI=1.05 to 1.16). Among children from the poorest and most affluent families respectively, 96.9% and 38.2% of post-legislation samples contained detectable cotinine. Socioeconomic gradients at higher exposure levels remained unchanged. Among children from the poorest families, 1 in 3 samples contained greater cotinine concentrations than Scottish bar worker's samples prior to legislation (3ng/ml). Smoking restrictions in homes and cars increased. However, little more than half (55.1%) of children, and only 19.3% of children of smokers, lived in smoke-free homes following legislation. Significant socioeconomic patterning remained, with 26.3% and 72.0% of children from the poorest and most affluent families respectively living in a smoke-free home. Conclusion: Urgent action is needed to reduce inequalities in SHS exposure. Such action should include emphasis on reducing smoking in cars and homes.